The effects of food deprivation and weight loss on food hedonics and the relative-reinforcing value of food - Cameron, Jameason (University of Ottawa (Canada), 2007)
Food is a primary reinforcer. There is strong evidence that when animals are chronically deprived of calories, the reward of a food stimulus becomes more salient. Recently leptin has been implicated in food reward. Typically the rewarding value of food is separated into the "liking" or pleasure/palatability component generated by the stimulus, and into the "wanting" or appetitive/incentive component. The goal of this current study was examine whether plasma leptin concentrations were related to food hedonics and food reinforcement in humans and to investigate the effect of food deprivation on these variables. Fourteen apparently healthy obese adults (n=9 women and 5 men; age=33.5+/-7.8) with BMI (kg/m2) between 30-45 were subjected to 8 weeks of caloric deprivation (-700kcal/day). Plasma leptin (ELISA), body weight and composition (DEXA), food reinforcement and food hedonics were measured pre- and post-intervention. Post weight loss palatability was rated significantly higher for the food reinforcers than that measured pre weight loss (p<0.01). No significant effect of the chronic food deprivation was noted for the reinforcing value of food. A significant negative correlation was observed between changes in palatability and those in body weight expressed as relative changes (r=-.62; p<0.05). No significant correlations were noted between changes in leptin and those in palatability or the reinforcing value of food. However, in a subgroup that lost the greatest percent of initial body weight (7-8%), food was more reinforcing post intervention (p<0.05). These findings demonstrate that chronic caloric deprivation can increase the subjectively rated palatability of preferred food items. The subgroup may be a caveat illustrating that a greater relative weight loss can lead to food becoming more rewarding.
Keywords: Health Sciences, Nutrition.; Health Sciences, Recreation.; Biology, Physiology.